Diseño de software no complicado - Dorin, Michael (2018)
The Agile Manifesto prescribes less focus on tools and processes, and more focus on human interactions. This is avery important and powerful concept; however, many development organizations have interpreted it in terms ofno procedures and no processes. This is understandable as many activities, such as the design workflow, are thanklessand laborious. When a proper design is missing, the resulting source code may become overly complicated anddifficult to maintain. The software design does not have to be arduous as this workflow can be done without painthrough an adaptation called Responsibility-Driven Design. This adaptation assigns personalities to the internalcomponents of the software to humanize the operation. The new design workflow is completely compatible withagile concepts such as customer interaction, and produces a credible candidate architecture ultimately resulting inthe creation of a less complicated software.